Association of low back pain and sleep quality with presenteeism. (14th December 2022) - Tezuka, M; Oka, T; Nakatsuka, K; Saeki, K; Ono, R
Abstract: Background: Low back pain (LBP) and poor subjective sleep quality (SSQ) are major risk factors for presenteeism. However, no studies have investigated whether combined LBP and poor SSQ are associated with presenteeism. Aims: We aimed to examine whether a combination of LBP and poor SSQ is associated with presenteeism. Methods: This cross-sectional study included 936 workers (median age, 38 years; men, 89%), with evaluated presenteeism using the work limitations questionnaire. We divided them into 'no presenteeism' and 'presenteeism' categories. The presence of LBP was defined as a numerical rating scale (NRS) score of ≥1 in current pain intensity. SSQ was assessed using a single question regarding whether the participants typically got enough sleep. We categorized the participants into four groups: (i) LBP + poor SSQ, (ii) non-LBP + poor SSQ, (iii) LBP + good SSQ and (iv) non-LBP + good SSQ. Logistic regression analysis was used to investigate the association between presenteeism and the presence of LBP and poor SSQ, adjusting for age, sex, work type, education, marital status, smoking status, body mass index and weekly working hours. Results: The data from 533 participants were used for analysis (median age, 38 years; men, 90%, response rate, 66%). Combined LBP and poor SSQ were significantly associated with presenteeism (non-LBP + poor SSQ: adjusted odds ratio = 0.56, 95% CI 0.32–0.96; LBP + good SSQ: 0.33, 0.20–0.56; non-LBP + good SSQ: 0.29, 0.18–0.48). Conclusions: Evaluating both LBP and SSQ may be beneficial in considering presenteeism. Abstract : This study aimed to examine whether a combination of low back pain (LBP) and poor subjective sleep quality (SSQ) is associated with presenteeism, which is reduced productivity while being ill or suffering from medical conditions at work, among Japanese workers. Our study showed that workers who did not present with either LBP or poor SSQ had lower risk of presenteeism than those with both LBP and poor SSQ.